On some morphological properties of the adjective in Gothic - Ratkus, Artūras (Kalbotyra, 2009)
The morphology of Gothic, as well as that of other older Germanic languages, has traditionally been analysed in phonological terms, with classifications that reflect earlier stages in the development of Germanic. This paper represents a pioneering attempt at applying the ‘canonical’ approach to the analysis of older Germanic, with a view to producing an adequate synchronic analysis of the morphological properties of the Gothic adjective. It is demonstrated that the traditional separation of strong and weak forms is synchronically unreasonable, and determination represents a non-canonical morphosyntactic feature of the Gothic adjective. Even though the traditional stemclass labels are obsolete from a synchronic point of view, synchronic form variation within Gothic adjective paradigms warrants distinguishing four inflectional classes, a classification which coincides with the traditional philological taxonomy. In addition to inflectional class, Gothic adjectives have been found to have stem indexing and syncretic index features.